A Force Control Test Rig for the Dynamic Characterization of Helicopter Primary Flight Control Systems. (2015) - Bertucci, Alessandro; Mornacchi, Andrea; Jacazio, Giovanni; Sorli, Massimo
Abstract: This paper describes an electronically controlled active force control system developed to test the tail rotor actuator of a new medium size helicopter. As for all hydraulic force control systems, the critical control issue is to mitigate the disturbance generated by the actuator velocity. For this particular case, the problem was accrued by the high bandwidth of the tail rotor actuator. To define the optimum control algorithm a model based approach was followed, estimating, when unable to measure directly, mechanical and hydraulic model parameters with a dedicated experimental campaign. A controller was eventually developed able to cope with the severe dynamic disturbances by introducing velocity and acceleration compensation laws. The controller was then implemented in a high recursion rate real time machine interfacing with a servovalve controlling the flow to a hydraulic actuator provided with hydrostatic bearings to minimize the friction force. The actuator force was sensed by a load cell providing the feedback signal for the force servoloop. A critical feature of the control was the need to develop a dedicated complex filter for the velocity signal able to cancel out the signal noise while allowing to retain the correct real time information of the actuator velocity and maintain adequate stability margins.